The Utilization Of Financial Information System To Support The Creation From Budget Costs Using e-Budgeting - Immaniar, Dewi; Mulyati, Mulyati; Putri Musliawati, Ulfatul Jannah (Pandawan, 2019)
In an era of modernization as this is now very much in the development of applications that make use of the computer program. One of them, namely the creation of the budget costs using e-budgeting application. What is the e-budgeting? E-Budgeting is a financial system that is stored online with the aim of transparency for each party. This system is applied as documentation for the preparation of the budget is usually in an area. Anyone can access data budget compiled by a local government so hopefully can prevent attempts of embezzlement of funds. The application of e-budgeting was chosen because it can bring cost transparency can be seen by anyone who is shown through the website. The results presented in this study is the use of proven e-budgeting nature of transparency compared with the way that still are conventional.